Skeletal Au prepared from Au–Zr amorphous alloys with controlled atomic compositions and arrangement for active oxidation of benzyl alcohol. Issue 21 (16th May 2016) - Nozaki, Ai; Tanihara, Yasutomo; Kuwahara, Yasutaka; Ohmichi, Tetsutaro; Mori, Kohsuke; Nagase, Takeshi; Yasuda, Hiroyuki Y.; Calers, Christophe; Louis, Catherine; Yamashita, Hiromi
Abstract : Residual ZrO2 in skeletal Au prepared from Au–Zr amorphous alloys contributed to an enhancement of the catalytic activity. Abstract : Skeletal (nanoporous) gold catalysts were prepared from Au–Zr amorphous alloys by immersion in HF solution to extract Zr moieties. The catalytic performance of the skeletal Au catalyst for the oxidation of benzyl alcohol to benzaldehyde was examined using O2 as an oxidant. The amount of benzaldehyde formed over skeletal Au treated with HF solution for 1 h was the highest among the prepared samples, despite the low surface area. Detailed characterization indicated that residual ZrO2 species on the skeletal Au promoted the oxidation reaction. The oxygen storage capacity (OSC) of skeletal Au was measured for the quantitative estimation of active sites and showed a positive correlation with the catalytic activity of skeletal Au, verifying the presence of Au–ZrO2 interfaces. Skeletal Au was also prepared from a Au–Zr crystalline alloy and its catalytic activity was compared with that of the one prepared from the amorphous alloy. The atomic arrangement of the Au–Zr amorphous alloy had a strong effect on the catalytic activity due to the surface structure (coordination number and morphology) of skeletal Au. The unsaturated Au atoms created in the skeletal Au catalysts contributed to the reduction of activation energy for oxidation of benzyl alcohol.